Graphene-Coated Elliptical Nanowires for Low Loss Subwavelength Terahertz Transmission - Da Teng; Kai Wang; Zhe Li; Yongzhe Zhao; Gao Zhao; Huiyong Li; Heng Wang (Applied Sciences, 2019)
Graphene has been recently proposed as a promising alternative to support surface plasmons with its superior performances in terahertz and mid-infrared range. Here, we propose a graphene-coated elliptical nanowire (GCENW) structure for subwavelength terahertz waveguiding. The mode properties and their dependence on frequency, nanowire size, permittivity and chemical potential of graphene are studied in detail by using a finite element method, they are also compared with the graphene-coated circular nanowires (GCCNWs). Results showed that the ratio of the long and short axes (b/a) of the elliptical nanowire had significant influence on mode properties, they also showed that a propagation length over 200 μm and a normalized mode area of approximately 10−4~10−3 could be obtained. Increasing b/a could simultaneously achieve both long propagation length and very small full width at half maximum (FWHM) of the focal spots. When b/a = 10, a pair of focal spots about 40 nm could be obtained. Results also showed that the GCENW had a better waveguiding performance when compared with the corresponding GCCNWs. The manipulation of Terahertz (THz) waves at a subwavelength scale using graphene plasmon (GP) may lead to applications in tunable THz components, imaging, and nanophotonics.